The Old Neo-Liberalism. The Neo-Liberalist Germ in Mises' and Hayek's Theories - Lamattina, Vanessa (PARTECIPAZIONE E CONFLITTO, 2016)
What is neo-liberalism? I’m going to affirm here that, as well as being a political doctrine born in the 1970s, neo-liberalism is the construction, the extension and the final reinforcement of a number of classical elements. My argument is that many of the typical aspects of contemporary neo-liberalism were already present in theories expressed by thinkers such as L. von Mises and F. A. von Hayek. As proof of this fact, I reclaim some characteristics of the present neo-liberal phenomenon as having been conceived by the above authors. These characteristics actually imply the ongoing spread of a dominant ideology that tends to pit the concept of liberty against those of rationality and critical consciousness. First, the article will analyse the changes that have occurred within the phenomenon of consumerism, which becomes en-twined with the competitive and entrepreneurial spirit of the individual; second, it will reflect on the wide-spread aversion to socialist policies, and in fact to all policies that provide for public intervention by the State and that change the relationship between State and economy; finally, it will relate these investiga-tions to the ideological and structural model that supports the European Union.